CURRICULUM PREPARATION TRAINING INDEPENDENT CAMPUS, FREEDOM TO LEARN (MBKM) IN STUDY PROGRAMS AS AN EFFORT TO MEET THE MAIN PERFORMANCE INDICATORS OF HIGHER EDUCATION - Mulyadi, Dedi; Utami, Tanti Kirana; Nur, Hilman; Kuswandi; Solihah, Cucu; Husaeni, Uus Ahmad; Paminto, Saptaning Ruju; Syaddad, Hasbu Naim (International Journal of Research -GRANTHAALAYAH, 2022)
The MBKM policy provides opportunities for students to gain more comprehensive learning experiences and new competencies through several learning activities. Service activities are carried out by holding two types of activities, namely the socialization of MBKM policies and workshops on preparing the MBKM curriculum. The target of this activity is the leadership of the study program, lecturers, and education staff; with this activity, the participants become more familiar with preparing the curriculum, starting from making learning outcomes to assessment techniques. Furthermore, the impact of this training realizes the fulfillment of higher education performance indicators.